Relationship Between Nematicity, Antiferromagnetic Fluctuations, and Superconductivity in FeSe1−xSx Revealed by NMR - Rana, Khusboo; Furukawa, Yuji (Frontiers in Physics, 2022)
The S-substituted FeSe, FeSe_1-xS_x, under pressure (p), provides a versatile platform for studying the relationship among nematicity, antiferromagnetism, and superconductivity. Here we present a short review of the recent experimental evidence showing that nematicity has a remarkable impact on the relationship between antiferromagnetic fluctuations and superconductivity. This has been revealed by several ^77Se nuclear magnetic resonance studies that have tracked the variability of antiferromagnetic fluctuations and superconducting transition temperature (T_c) as a function of x and p. T_c is roughly proportional to antiferromagnetic fluctuations in the presence or absence of nematic order suggesting the importance of antiferromagnetic fluctuations in the Cooper pairing mechanism in FeSe_1-xS_x. However, the antiferromagnetic fluctuations are more effective in enhancing superconductivity in the absence of nematicity as compared to when it is present. These experimental observations give renewed insights into the interrelationships between nematicity, magnetism, and superconductivity in Fe-based superconductors.